2020
DOI: 10.1038/s41467-020-18241-x
|View full text |Cite
|
Sign up to set email alerts
|

Insights into projected changes in marine heatwaves from a high-resolution ocean circulation model

Abstract: Global climate models project the intensification of marine heatwaves in coming decades due to global warming. However, the spatial resolution of these models is inadequate to resolve mesoscale processes that dominate variability in boundary current regions where societal and economic impacts of marine heatwaves are substantial. Here we compare the historical and projected changes in marine heatwaves in a 0.1°ocean model with 23 coarser-resolution climate models. Western boundary currents are the regions where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
65
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 44 publications
4
65
0
Order By: Relevance
“…outputs from all the selected GCMs were not available at the time this study was launched, so whether the mechanisms behind the extreme events will change could not be assessed. Nevertheless, recent studies have confirmed the results of [18] showing that the driver for MHW changes in most regions of the world is the change in the mean state, rather than changes in the intra-seasonal variability [7,38]. Therefore, here we focus on assessing how the changes in the mean state would modify the statistics of MHWs in the Red Sea and the Gulf of Aden.…”
Section: Plos Onementioning
confidence: 85%
“…outputs from all the selected GCMs were not available at the time this study was launched, so whether the mechanisms behind the extreme events will change could not be assessed. Nevertheless, recent studies have confirmed the results of [18] showing that the driver for MHW changes in most regions of the world is the change in the mean state, rather than changes in the intra-seasonal variability [7,38]. Therefore, here we focus on assessing how the changes in the mean state would modify the statistics of MHWs in the Red Sea and the Gulf of Aden.…”
Section: Plos Onementioning
confidence: 85%
“…Climate change is projected to increase sea temperature mean and variability (Hayashida et al, 2020; Hurd et al, 2018). Consequently, species with narrower temperature tolerance are more likely to be negatively impacted by these environmental changes (Perry et al, 2005; Sunday et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Climate change is projected to increase sea temperature mean and variability (Hayashida et al, 2020;Hurd et al, 2018). Consequently, F I G U R E 1 Conceptual schematic drawing of the CRA framework applied to our specific study.…”
Section: Temperature Tolerance Rangementioning
confidence: 99%
“…Western boundary currents (WBCs) are global warming hot-spots (Popova et al, 2016;Wu et al, 2012) where MHWs have been found to be more intense and frequent (Hayashida et al, 2020). WBCs, such as the Kuroshio Current, Agulhas Current and the EAC, are areas of strong poleward advection that are characterised by large sea surface temperature (SST) variability.…”
mentioning
confidence: 99%